2007
DOI: 10.2754/avb200776s8s067
|View full text |Cite
|
Sign up to set email alerts
|

Change of Colour and pH-value in Pheasant Meat after Exposure to Ionizing Radiation

Abstract: Dvořák P., J. kunová, M. vodňanský: Change of Colour and pH-value in Pheasant Meat after Exposure to Ionizing Radiation. Acta vet. Brno 2007, 76: S67-S71.The purpose of this paper was to study the impact of ionizing radiation on the changes of colour and the pH-value of pectoral and femoral musculature in pheasants (Phasianus colchicus). The parameters of colour L*, a* and b* were observed before irradiation (24 hours post mortem) and after irradiation ( 60 Co source, doses of 2.5 and 5 kGy). Reduction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Higher L* values (54.2 or 56.6) were obtained by Hofbauer et al (2010). In our study, a* values of breast muscles of the analysed pheasants were higher, and b* values lower than those reported by Dvořák et al (2007) and Hofbauer et al (2010).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Higher L* values (54.2 or 56.6) were obtained by Hofbauer et al (2010). In our study, a* values of breast muscles of the analysed pheasants were higher, and b* values lower than those reported by Dvořák et al (2007) and Hofbauer et al (2010).…”
Section: Discussioncontrasting
confidence: 66%
“…Over the last ten years, pheasants have been the subject of many studies which investigated their growth and body conformation Kokoszyński et al, 2011), structure and development of the digestive tract and other internal organs (Hell et al, 2003;Marzoni et al, 2005;Brudnicki et al, 2008;Baohua et al, 2010;Kokoszyński et al, 2010), dressing percentage and carcass composition Adamski and Kuzniacka, 2006;Kokoszyński et al, 2008), chemical composition of meat Straková et al, 2006;Kuzniacka et al, 2007;Litwinczuk et al, 2007;Brudnicki et al, 2010), as well as physicochemical and sensory properties of pheasant meat (Dvořák et al, 2007;Kuzniacka et al, 2007;Hofbauer et al, 2010).…”
mentioning
confidence: 99%
“…There are also studies found the breast meat lightness lower. Fernye et al (2017) and Dvořák et al (2007) reported the breast meat lightness of pheasant breast meat to 49.27 and 41.19, respectively. Different factors could have effect on this variation.…”
Section: Resultsmentioning
confidence: 99%
“…Yook et al (2001), reported that in Korean cattle meat irradiated one day after slaughter, pH decreased more rapidly in irradiated muscle than in non-irradiated samples during storage at 4°C. In contrast, Dvořák et al (2007), reported that there was some increase in pH of pheasant meat on irradiation.…”
Section: Resultsmentioning
confidence: 94%